Indian Woods for Textile Mill Accessories - Part IV (Indian Timbers for Picker Arms) - Rehman, M. A.; Askari, Mord. (Indian Forester, 1956)
This paper gives the results of service tests carried out in several cotton mills on picker arms made of Indian woods. It has been found that dhaman (Grewia tiliaefolia) gives as good a life as hickory imported from America. Axlewood (Anogeissus latifolia), babul (Acacia arabica), lendi (Lagerstroemia parviflora), tendu (Diospyros melanoxylon), and sandan (Ougeinia dalbergioides) can also be used satisfactorily for this purpose. The manufacture of picker arms can be carried out on cottage industry basis, using only simple machinery.